"Metateoretyczne" założenia pedagogiki teonomicznej i teonomicznej dydaktyki literatury = Metatheoretical concepts of teonomic pedagogy and teonomic didactics of literature - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The author describes the metatheoretical concepts of teonomic pedagogy (based of the law of God) and teonomic didactics of literature. The concepts are homogeneous, since we can talk about the correspondence of general objectives of education as well as the objectives of literary education. In the context of theological divagations and Christian visions of humanity and the world, the author ponders the thesis that literary education should of be service to God and in God.
Keywords: teonomia; pedagogika; dydaktyka literatury